2007
DOI: 10.1152/ajprenal.00175.2006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic drugs and spinal cord transections indicate that different spinal circuits are involved in external urethral sphincter activity in rats

Abstract: Chang H-Y, Cheng C-L, Chen J-JJ, de Groat WC. Serotonergic drugs and spinal cord transections indicate that different spinal circuits are involved in external urethral sphincter activity in rats. Am J Physiol Renal Physiol 292: F1044 -F1053, 2007. First published October 17, 2006; doi:10.1152/ajprenal.00175.2006.-Lower urinary tract function is regulated by spinal and supraspinal reflexes that coordinate the activity of the urinary bladder and external urethral sphincter (EUS). Two types of EUS activity (toni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
128
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(139 citation statements)
references
References 28 publications
10
128
1
Order By: Relevance
“…Marson 15 and Lee et al 16 found that neurons in the dorsal gray commissure activated with the pudendal or pelvic nerve stimulation might integrate afferent signal neurons within multiple spinal segments and relay important sensory information to the brain in spinally intact rats. On the other hand, Dolber et al 17 and Chang et al 11 proposed a hypothetical framework for the coordinated bladder contraction and bursting EUS relaxation in the SCI rats including a capsaicin-insensitive afferent input to a switch, which directly or indirectly controls excitation of the parasympathetic preganlionic neurons and relaxation of the Onuf's nucleus motor neurons. In our study, BMSCs in the dorsal gray commissure, presenting proximal to both the sacral parasympathetic preganglionic neurons and the spinal EUS pattern generator, may promote the formation of the switch to coordinate bladder contraction and EUS relaxation by expressing neuronal and astroglial markers 18 or secreting neurotrophic factor and cytokine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marson 15 and Lee et al 16 found that neurons in the dorsal gray commissure activated with the pudendal or pelvic nerve stimulation might integrate afferent signal neurons within multiple spinal segments and relay important sensory information to the brain in spinally intact rats. On the other hand, Dolber et al 17 and Chang et al 11 proposed a hypothetical framework for the coordinated bladder contraction and bursting EUS relaxation in the SCI rats including a capsaicin-insensitive afferent input to a switch, which directly or indirectly controls excitation of the parasympathetic preganlionic neurons and relaxation of the Onuf's nucleus motor neurons. In our study, BMSCs in the dorsal gray commissure, presenting proximal to both the sacral parasympathetic preganglionic neurons and the spinal EUS pattern generator, may promote the formation of the switch to coordinate bladder contraction and EUS relaxation by expressing neuronal and astroglial markers 18 or secreting neurotrophic factor and cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Segments 40 mm rostral and caudal to the site of injury were paraffin embedded as well as lumbar level 3-4 (L 3À4 ), as this neurons in L 3À4 were involved in the generation of EUS bursting activity during voiding. 11 A series of adjacent 6 mm coronal or longitudinal sections were cut and a section of each block of the spinal cord was stain with hematoxylin/eosin (H/E). Immunohistochemistry for BrdU was performed on serial sections using the avidin-biotin complex method.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Multiple neurotransmitters in the spinal cord have been postulated to mediate sexual and bladder reflexes including glutamate, acetylcholine, oxytocin, serotonin and various peptides [3,10,27,58,59,66,69,70]. The present study examined the relationship of VGlut2, VGlut3 transporters and NKI receptors with fos-I nuclei as both glutamate and NKI receptors have been shown to regulate pelvic reflexes [64,69].…”
Section: Discussionmentioning
confidence: 97%
“…Rats are usually anesthetized with urethane or ketamine and xylazine intraperitoneally for EMG recordings (Chang et al 2007;Chang & Havton 2008;Jiang et al 2009aJiang et al , 2009bPikov et al 1998). Sometimes isoflurane is used to supplement anesthesia during surgical preparation for the recording (Miyazato et al 2008).…”
Section: Techniques For Recording Emg Of Pelvic Floor Muscles In Ratsmentioning
confidence: 99%